Rocní analýza individuálního tréninkového procesu v hodu kladivem - Kralova, T. (2015)
The thesis is focused on the theoretical basis of sports training of the hammer throw. In the research section is discussed the annual training cycle of the hammerthrower T.K. in terms of the general and the special training indicators, comparison the test indicators and evaluate the intensity of load in seven days before the each event in 2014.